If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + -31) + 2x = 72 Reorder the terms: 2(-31 + 5x) + 2x = 72 (-31 * 2 + 5x * 2) + 2x = 72 (-62 + 10x) + 2x = 72 Combine like terms: 10x + 2x = 12x -62 + 12x = 72 Solving -62 + 12x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '62' to each side of the equation. -62 + 62 + 12x = 72 + 62 Combine like terms: -62 + 62 = 0 0 + 12x = 72 + 62 12x = 72 + 62 Combine like terms: 72 + 62 = 134 12x = 134 Divide each side by '12'. x = 11.16666667 Simplifying x = 11.16666667
| 8/4+39/8=p | | (4y-8)/3y=6 | | 3x^2+2-16=0 | | 2(5x-31)(2w)=72 | | 2y^3+y^2-50y-75= | | -4x^2+(-7x)+(-4)+3x^2+8x+(-4)= | | -36x=3(6y-6) | | 4y-8/3y=6 | | 2(5x-31)+2x= | | X-8/4=7 | | 3x+2xy-5+x+3xy+10= | | 6/x=3/7 | | 480-8y=8 | | -2=w/-5 | | 6+w=12 | | 2(5x-31*x)= | | 9e-2=5e+26 | | 22x+26=48 | | y=0(8)+8 | | 120=(x+1)(x+20) | | 10/5x^2-20x-60=0 | | 3/4*6=c | | 2(5x-31)(2x)= | | -7(x+1)=43 | | -27+s=42 | | p+1/4/3=4/5/8 | | 26-2x=16 | | 6x^2+(-10x)+6+4x+(-5)= | | 22-2=4 | | -5x+6(3x-6)=-15-8x | | 7(2x+5)-7=32 | | 2x+(-6x)+(-5x)= |